Relationship between hemodynamic parameters and portal venous pressure in cirrhosis patients with portal hypertension - Yao, Hongjuan (Open Life Sci, 2020)
Cirrhosis caused by viral and alcoholic hepatitis is an essential cause of portal hypertension (PHT). The incidence of PHT complication is directly proportional to portal venous pressure (PVP), and the clinical research of PVP and its hemodynamic indexes is of great significance for deciding the treatment strategy of PHT. Various techniques are currently being developed to decrease portal pressure but hemodynamic side effects may occur. In this article, the hemodynamic indexes of cirrhotic PHT patients were studied to explore the correlation between the index and PVP and to evaluate the clinical value of Doppler ultrasound in measuring PVP in patients with PHT. This was achieved by selecting 90 cirrhotic PHT patients who underwent transjugular intrahepatic portosystemic shunt in our hospital from June 2015 to September 2019. Fifty healthy people who had a physical examination in the hospital in the same period were selected as the control group. The liver hemodynamic parameters of two groups were measured by Doppler ultrasound, and the cirrhotic PHT patients were graded by the Child–Pugh grading method to evaluate the liver function and measure the PVP value. The results showed that both the central portal vein velocity (PVV) and splenic vein velocity (SVV) of the PHT group were lower than those of the control group. Also, the portal vein diameter (PVD), portal venous flow and splenic vein diameter (SVD) were higher than those of the control group (all Ps < 0.05). Among liver function graded PHT patients, the PVD, PVV, SVD and SVV were significantly different (all Ps < 0.05). Furthermore, the PVP of patients with liver function grades A, B and C was 38.9 ± 1.4, 40.6 ± 5.1 and 42.5 ± 4.8 cmH(2)O, respectively, with a significant difference. It can be concluded from this study that Doppler ultrasound can be used as a tool for clinical assessment of PHT in cirrhosis patients. Doppler ultrasound showed a good prospect in noninvasive detection of PHT in cirrhosis; however, this technique needs application on large sample population study to validate the results.